Entre soft power e sharp power: A diplomacia pública da China durante o combate à pandemia de COVID-19 - Santos, Niedja De Andrade E Silva Forte Dos (2021)
The research aims to identify how China articulated soft and sharp power while fighting the COVID-19 pandemic. The main argument is that the articulation be tween soft and sharp power is an inherent characteristic of Chinese public diplo macy. This argument features soft power as a power style operating not only in the international dimension, but also in the domestic dimension. After China’s contex tualization, the analytical matrix was built from the operationalization of key con cepts, namely public diplomacy, soft power and sharp power, paying attention to Chinese characteristics. The case study was led with data collected from primary and secondary sources. Besides the indication of paths for future developments, the conclusion summarizes how Chinese public diplomacy managed soft and sharp power with positive results in the international sphere and suggests that incorporat ing sharp power to diplomatic toolbox may be useful.